Association of salivary steroid hormones and their ratios with time-domain heart rate variability indices in healthy individuals - Mazgelytė, Eglė; Chomentauskas, Gintaras; Dereškevičiūtė, Edita; Rekienė, Virginija; Jakaitienė, Audronė; Petrėnas, Tomas; Songailienė, Jurgita; Utkus, Algirdas; Kučinskienė, Zita Aušrelė; Karčiauskaitė, Dovilė (Journal of Medical Biochemistry, 2020)
Backgound: Stress system consists of the hypothalamic-pituitary-adrenal (HPA) axis and the locus caeruleus/norepinephrine-autonomic nervous system (ANS). Traditionally, HPA axis activity is evaluated by measuring its end-product cortisol while the activity of ANS is assessed using heart rate variability (HRV) indices. Alterations in cortisol levels and HRV measures during laboratory-based stress tasks were extensively studied in previous research. However, scarce data exist on the associations of HRV measures with the levels of other adrenal steroid hormones under baseline conditions. Thus, we aimed to evaluate the activity of HPA axis by measuring salivary cortisol, cortisone, dehydroepiandrosterone (DHEA) levels and their ratios and to examine its association with HRV measures in a sample of healthy young and middle-aged adults.Methods: For each participant (n=40), three data collection sessions taking place at the same time of the day were scheduled within five working days. Participants completed a self-reported questionnaire on sociodemographic and lifestyle characteristics, filled out Perceived Stress Scale and State-Trait Anxiety Inventory. Also, saliva samples were collected and physiological measures including resting HR and HRV were recorded during three data collection sessions.Results: Statistically significant associations between diminished parasympathetic vagal tone evaluated by time-domain HRV measures and higher salivary cortisol, lower DHEA levels, as well as increased DHEA to cortisol ratio were found. Also, physiological stress indicators (i.e. HRV) showed greater intrindividual stability compared with biochemical biomarkers (i. e. salivary steroid hormones) within the period of five days.Conclusions: Our findings suggest that both cortisol and DHEA mediate the link between two stress-sensitive homeostatic systems.